1984
DOI: 10.1111/j.1432-1033.1984.tb08470.x
|View full text |Cite
|
Sign up to set email alerts
|

Baker's yeast flavocytochrome b2

Abstract: It has been shown that reduced flavocytochrome b2 not only catalyzes reduction of bromopyruvate [P. Urban, P.M. Alliel and F. Eur. J. Biochem. 134,275 -2811 but also transforms it into pyruvate in a reductive elimination process. The dehydrohalogenation reaction also takes place when oxidized enzyme acts on bromolactate, but the reaction is more difficult to observe under these conditions because of its low efficiency compared to the normal oxidative process. The maximal rates of pyruvate production from brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…These results are in keeping with the hydride ion transfer mechanism that was recently proposed for another member of the ␣-hydroxy acid oxidase superfamily, flavocytochrome b 2 , based on primary and solvent deuterium kinetic isotope effects on the wild type and selected active site mutant enzymes (35)(36)(37). The results are also consistent with the alternative proposal that the initial abstraction of a proton is not occurring on the hydroxyl group of glycolate but instead on the substrate ␣-carbon to generate an activated carbanion species that goes on to form a covalent intermediate with the N(5) atom of the enzyme-bound FMN, as previously proposed by other groups for flavocytochrome b 2 and mandelate dehydrogenase (5,19,38,39). Irrespective of the mechanism of substrate activation (i.e.…”
Section: Discussionsupporting
confidence: 78%
“…These results are in keeping with the hydride ion transfer mechanism that was recently proposed for another member of the ␣-hydroxy acid oxidase superfamily, flavocytochrome b 2 , based on primary and solvent deuterium kinetic isotope effects on the wild type and selected active site mutant enzymes (35)(36)(37). The results are also consistent with the alternative proposal that the initial abstraction of a proton is not occurring on the hydroxyl group of glycolate but instead on the substrate ␣-carbon to generate an activated carbanion species that goes on to form a covalent intermediate with the N(5) atom of the enzyme-bound FMN, as previously proposed by other groups for flavocytochrome b 2 and mandelate dehydrogenase (5,19,38,39). Irrespective of the mechanism of substrate activation (i.e.…”
Section: Discussionsupporting
confidence: 78%
“…Since then, we have found that, under appropriate conditions, flavocytochrome b2 can catalyze halide ion elimination from /3-halogeno substrates and have predicted that similar conditions would enable the observation of hydroxyacid oxidase catalyzed elimination (Urban & Lederer, 1984;. In this paper, we report experiments that verify our hypothesis.…”
supporting
confidence: 57%
“…On the contrary, since the net charge of the nitro group is zero, one might suggest that the negative character of its oxygen atoms is insufficient to afford satisfactory neutralization of the Arg-376 charge. In conclusion, it appears that the active site of flavocytochrome b2 [9,12] provides an example of how an enzyme can dissipate the electrostatic potential of a carboxylate by hydrogen-bonding and ion-pairing, so that a-carbanion formation becomes energetically feasible. Why is there no redox reaction between ethane nitronate and flavocytochrome b2?…”
Section: Discussionmentioning
confidence: 99%